Yersiniosis and acute secondary axonal sensorimotor polyneuropathy: a case report - A. Daškevičiūtė; R. Mameniškienė (Neurologijos seminarai)
Yersiniosis is a diarrheal illness that usually causes acute gastroenteritis, pseudoappendicitis syndrome, erythema nodosum or reactive arthritis. On rare occasions, yersiniosis can be a cause of meningitis. Causes of axonal sensorimotor polyneuropathy may be infectious, but only few cases of peripheral nervous system damage caused by jersiniosis have been reported. This article presents a case of yersiniosis which presented with febrile fever and severe inflammatory response. At the onset of the disease, Guillain–Barre syndrome was suspected but later acute axonal sensorimotor polyneuropathy was diagnosed. There were no other causes of peripheral neuropathy detected and we assume that yersiniosis was the cause of acute axonal sensorimotor polyneuropathylanguage most frequently inhibited EDs in patients with focal epilepsy and reading in an unknown language had the same effect on patients with generalized epilepsy.